Сарматське поховання з тамгами на території Ольвійської держави - Симоненко, О.В. (Археологія, 1999)
У статті досліджується поховання, виявлене 1918 р. поблизу с. Козирки. На підставі знайдених матеріалів автор вважає, що воно належало багатші сарматам, які мешкали на території Ольвійської держави наприкінці І—початку II ст. н. е. В 1918 г. местный житель раскопал близ с. Козырки захоронение в склепе. Немецкий археолог Т. Виганд приобрел у него часть вещей и описал захоронение в дневнике. Погребение было парным, скелеты находились в дощатых гробах. При них обнаружены лук и стрелы, меч, серебряная бляха конского нагрудника с тремя кольцами, фибула, туалетный флакон, золотая бляшка, амфора, деревянные сосуды и музыкальный инструмент типа арфы. На сосуды и арфу были нанесены 36 тамг. По совокупности датирующего инвентаря и схемам тамг погребение датируется концом I — началом II в. н. э. Оно принадлежало богатым сарматам, очевидно, проживавшим на территории Ольвийского государства. Не исключено, что они были представителями сарматских правителей Фарзоя и Инисмея, в союзе с которыми находилась в это время Ольвия. In 1918 the local villager dug out the grave in the catacombe close to Kozyrka village. The German archaeologist T.Wigand has acquired from him a part of found goods and described this grave in his diary. The tomb was double, the skeletons lay in the plank coffins. The grave goods consisted of wooden vessels and musical tools of the harp type, bows, and arrows, swords, a silver phalera with three rings, decorating the horse breast collar, fibula, toilet bottle, golden plaque, and amphora. 36 tamga-signes were drawn onto the vessels and harp. According to the dating goods and scheme of the tamgas the grave is dated to the end of 1st - beginning of the 2nd cent. A.D. It belonged to the rich Sarmatians who obviously lived on the territory of Olbian state. Is not excluded that they were the representatives of the Sarmatian chiefs Farzoios and Inismeios with whom at this time Olbia was in alliance.